HUBUNGAN DUKUNGAN KELUARGA DENGAN SELF CARE MANAGEMENT PADA LANSIA HIPERTENSI DI DESA KUTAYASA - Kharisma Putri Nur Aeni; Siti Khoiriyah; Sri Mulyani; Fifi Alviana (Jurnal Ilmiah Kesehatan, 2025)
The most common disease suffered by people in Indonesia and increasing is hypertension. Prevention of hypertension can be done one of them with self-care management. The achievement of successful hypertension self-care management behavior driven by the family support received by the elderly, the better the self-care management in the elderly. The purpose of this study was to determine the relationship between family support and self-care management in hypertensive elderly in Kutayasa village. The type of research used quantitative research with a non-experimental research design used a cross sectional approach. The population were elderly people suffering from hypertension in Kutayasa Village. The sample amounted to 69 respondents. The sampling technique used purposive sampling. Data analysis used the Spearman-Rank statistical test. The results showed that the p-value was 0.011 or <0.05. It can be concluded that there were a relationship between family support and self-care management in elderly hypertension in Kutayasa Village.